A One‐Pot "Triple‐C" Multicyclization Methodology for the Synthesis of Highly Constrained Isomerically Pure Tetracyclic Peptides. (2nd August 2018) - Richelle, Gaston J. J.; Schmidt, Marcel; Ippel, Hans; Hackeng, Tilman M.; van Maarseveen, Jan H.; Nuijens, Timo; Timmerman, Peter
Abstract: A broadly applicable one‐pot methodology for the facile transformation of linear peptides into tetracyclic peptides through a chemoenzymatic peptide synthesis/chemical ligation of peptides onto scaffolds/copper(I)‐catalyzed reaction (CEPS/CLIPS/CuAAC; "triple‐C") locking methodology is reported. Linear peptides with varying lengths (≥14 amino acids), comprising two cysteines and two azidohomoalanines (Aha), were efficiently cyclized head‐to‐tail by using the peptiligase variant omniligase‐1 (CEPS). Subsequent ligation–cyclization with tetravalent (T41/2 ) scaffolds containing two bromomethyl groups (CLIPS) and two alkyne functionalities (CuAAC) yielded isomerically pure tetracyclic peptides. Sixteen different functional tetracycles, derived from bicyclic inhibitors against urokinase plasminogen activator (uPA) and coagulation factor XIIa (FXIIa), were successfully synthesized and their bioactivities evaluated. Two of these (FF‐T41/2 ) exhibited increased inhibitory activity against FXIIa, compared with a bicyclic control peptide. The corresponding hetero‐bifunctional variants (UF/FU‐T41/2 ), with a single copy of each inhibitory sequence, exhibited micromolar activities against both uPA and FXIIa; thus illustrating the potential of the "bifunctional tetracyclic peptide" inhibitor concept. Abstract : Completing the circle : A one‐pot methodology for the facile synthesis of isomerically pure tetracyclic peptides is reported. The methodology is useful in high‐throughput library formats and a set of 16 bifunctional tetracyclic peptides show good activities against two non‐homologous enzymes, thereby emphasizing the potency of this compound class.